THE LEVEL OF SATISFACTION WITH AN ERP SYSTEM IN RELATION TO THE DECISION MAKING PROCESS - Claudia van der Vorst (European Scientific Journal, ESJ, 2014)
This paper investigates in the buying behavior of small and mid-size companies in Germany with a special focus on the decision making process, the buying process, in cases of purchasing information technology / ERP (Enterprise Resource Planning) systems. Furthermore it will outline the connection of the decision making and buying process and the success of the implementation, reviewing critical success factors for the implementation of the ERP system. Especially for small and mid-size companies (SME) the decision to buy a specific software package will have significant consequences for all parts of the business in terms of business processes and costs. The paper will support hypotheses about the acquisition of an ERP system at SME companies. Success factors will be identified, prioritized and evaluated specifically for the requirements of the small and medium size companies. Findings are that during the acquisition phase the entire company is expected to support the definition of requirements of the new system, the purchasing department has to be supported strongly by strategic guidelines of the top management, a business case needs to be prepared in the very beginning and the long term vision needs to be challenged with the capabilities of the new system. After a long implementation process and after go live none of the requirements are reviewed again nor measured to ensure this strategic investment was executed according to the defined expectations.